1999
DOI: 10.1046/j.1365-2141.1999.01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐minimization analysis of CHOP, fludarabine and rituximab for the treatment of relapsed indolent B‐cell non‐Hodgkin's lymphoma in the U.K.

Abstract: Summary. The optimal therapy for patients with relapsed indolent B-cell non-Hodgkin's lymphoma is unclear. Combination chemotherapy such as CHOP (cyclophosphamide, doxorubicin, vincristine, prednisolone) or purine analogues including¯udarabine are frequently used and the anti-CD20 monoclonal antibody rituximab has recently been licensed for use. However, no comparative studies of these therapies have been reported. Since relapsed indolent B-cell NHL is generally regarded as incurable with current therapies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 20 publications
2
31
0
1
Order By: Relevance
“…The drug cost of CHOP has been derived from papers by Sweetenham and colleagues 83 and Beard and colleagues. 84 The cost per course of CHOP based on Sweetenham and colleagues was £172.50, whereas Beard and colleagues estimated the cost to be £160, ranging to £283 if one assumes a 50% chance of neutropenic sepsis.…”
Section: Treatment Cost Of Chop and R-chop Regimensmentioning
confidence: 99%
“…The drug cost of CHOP has been derived from papers by Sweetenham and colleagues 83 and Beard and colleagues. 84 The cost per course of CHOP based on Sweetenham and colleagues was £172.50, whereas Beard and colleagues estimated the cost to be £160, ranging to £283 if one assumes a 50% chance of neutropenic sepsis.…”
Section: Treatment Cost Of Chop and R-chop Regimensmentioning
confidence: 99%
“…Herold et al [12, 13] reported costs for Canada, Germany and Italy, and it is difficult to compare these findings with our own. Sweetenham et al [15] reported the findings of a UK cost-minimization analysis comparing CHOP, fludarabine and rituximab with costs (in 1998) calculated from the perspective of the hospital. CHOP and fludarabine treatment costs were estimated from resource events occurring in one cycle of treatment while rituximab costs were calculated on the basis of trial data collected across the whole treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the unit costs associated with OP episodes were varied by ±20%. This method follows the sensitivity analyses in previous studies [15, 18] and explores variations in cost between different trusts [6]. Thirdly, we included the cost of AEs occurring after the end of active treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations